Interfacial control of PVDF-TrFE/SWCNT nanocomposites using P3HT-PMMA block copolymer for ultra-low percolation threshold - Cho, Kie Yong; Lee, Yun-Jae; Kim, Hyun-Ji; Yoon, Ho Gyu; Hwang, Seung Sang; Han, Yang-Kyoo; Baek, Kyung-Youl (ELSEVIER SCI LTD, 2015)
Poly(vinylidenefluoride-co-trifluoroethylene) (PVDF-TrFE)/SWCNT nanocomposites with ultra-low percolation threshold were prepared by interfacial control using a block copolymer comapatibilizer. For this, a well-defined block copolymer of poly(3-hexylthiophene) (P3HT) and poly(methyl methacrylate) (PMMA) (P3HT-b-PMMA) was synthesized by combination of GRIM and ATRP (M-n = 24 K, M-w/M-n = 1.25), where the P3HT block segment wrapped the SWCNTs by pi-pi interaction and the resulting PMMA block segment dangled from the SWCNTs, which gave de-bundled SWCNTs without any aggregations for over 5 months in most common organic solvents for PMMA. The block copolymer coated SWCNT (TMCNT) was then mixed with PVDF-TrFE to prepare PVDF-TrFE/SWCNT nanocomposites (PVT-TMCNT), which enabled excellent dispersion of SWCNT in a PVDF-TrFE matrix without aggregation due to the miscibility of the PMMA on TMCNT and PVDF-TrFE. Obtained PVT-TMCNT showed large enhancements of the electrical conductivity and the dielectric constant with ultra-low percolation threshold (f(c) = 0.07 wt.%) due to excellent interfacial control by the block copolymer comapatibilizer between SWCNT and PVDF-TrFE. Improved ferroelectric properties of PVT-TMCNT were also observed by an increase of field-induced polarization response, which was almost over 10-times higher than for neat PVDF-TrFE. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: HIGH DIELECTRIC-CONSTANT; CARBON NANOTUBES; POLY(VINYLIDENE FLUORIDE); ELECTRICAL-PROPERTIES; POLYMER COMPOSITES; PERMITTIVITY; ENHANCEMENT; CONDUCTIVITY; TEMPERATURE; ELASTOMERS